Strangulated hiatal hernia: About a new observation - Estrugo, Roberto Luis (Cirugía del Uruguay, 1978)
The paper refers to one more case of strangled hiatus herniation, of the gastric volvulus variety. Treatment should always be surgical, regardless of improvement and even disappearence of symptoms brought about by introduction of a nasogastric cathete. The author dwells on sone valuable technical aspects of nasogastric catheterization and on surgical details involved in the liberalization of the mediastinal gastric bursal and expresses his belief that these manoeuvres made possible a satisfactory surgical soIution.